Plataforma en línea para foros y comunidades colaborativas enfocadas en la resolución de problemas en los sectores de agricultura y tecnología - Celorio Malavé, Jahir Alexander (2025)
The graduation project aimed to develop an interactive digital platform that promotes collaboration and knowledge exchange among stakeholders in the agricultural sector in Bolívar canton. The Extreme Programming (XP) methodology was employed, and during the planning phase, user stories were defined through semi-structured interviews, and requirements were documented following the IEEE 830 standard. The design phase included UML diagrams and prototypes in Figma, while development was carried out using Laravel and Angular, integrating authentication via Firebase. Testing involved PHPUnit, JMeter, and K6. Design patterns and SOLID principles were applied, enabling the construction of a scalable and maintainable architecture. As a result, a functional platform was obtained, featuring forums, personalized profiles, and a reputation system, which helps close digital gaps in rural areas.